INTEGRATED MARKETING COMMUNICATION DAN PERSONAL BRANDING DALAM MENINGKATKAN BRAND EQUITY USAHA MAMITOKO - Lubis, Wahya Iffa; Fahdillah, Yosi; Muryati (LPPM Universitas Dinamika Bangsa, 2025)
Abstract Disruption is the background for rapid changes in several aspects of life, one of which is progress and the role of technology in human life. So that it affects the practice of the business world which is increasingly competitive. Cake By Nadia (CBN) is a business brand founded by Nadia Indah Pratiwi which focuses on selling cake and dessert products. Nadia takes advantage of technological sophistication in carrying out her business activities and marketing. The study was conducted using the basic of marketing mix and integrated marketing communication sciences to describe the process of marketing activities of CBN and by using the theory of the eight laws of personal branding to find out how the personal branding can be formed of CBN owners and its affect the brand equity of CBN businesses.The results of the study describe the practice of integrated marketing communication in fulfilling the eight elements in building Nadia's personal branding. Nadia uses Instagram, whatsapp, and Tiktok applications in the practice of integrated marketing communication (IMC) so that she is able to display online and offline activities on social media which ultimately affects the perception of many people towards her. There is a correlation between integrated marketing communication (IMC) and personal branding that is formed in increasing the brand equity of CBN business. Keywords: IMC, Instagram, Whatsapp, Cake By Nadia, Personal Branding, Brand Equity